Physiochemical Characteristics Analysis of Garrah River Water at Shahjahanpur, Ganga River Basin, Uttar Pradesh, India - Sahay Abhinav; Kumar Umesh; Kumar Kundan; Prasad Bhatt Sunil; Ranjan Kumar Amit; Mahadeva Rajesh; Gupta Vinay; Dixit Saurav (BIO Web of Conferences, 2024)
This study focuses on the physiochemical analysis of the Garrah River in Shahjahanpur, within the Ganga River Basin, Uttar Pradesh, India. The research evaluates the impact of various pollutants, including industrial and municipal sewage, on the river's water quality. Water samples were collected from three locations along the river, representing different pollution levels. The analysis included parameters such as pH, dissolved oxygen (DO), total suspended solids (TSS), color, odor, electrical conductivity, temperature, chemical oxygen demand (COD), salinity, and the concentrations of various elements. The findings showed variations in water quality parameters, with DO, TSS, COD, and heavy metals indicating significant pollution, particularly downstream. Color and odor also suggested pollution from nearby industries. The study revealed that some parameters exceeded WHO standards for drinking water, raising concerns about health risks from exposure to contaminants like chromium. Urgent actions are required to treat municipal sewage and industrial effluents before discharging into the Garrah River. This research highlights the need for ongoing monitoring and sustainable management of water resources in the Ganga River Basin to protect the ecosystem and local communities. It underscores the importance of improving water quality in the region.